Bentuk-Bentuk Interaksi Mahasiswa KPM dengan Masyarakat Kecamatan Bukit Kabupaten Bener Meriah: Studi di Desa Serule Kayu dan Desa Kute Tanyung - Juhari; Yusran Nasir (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2024)
The main problem of this research is based on the phenomenon of students' inability to interact with people outside of campus, so that they are often viewed cynically by societies. The location of the research is in Serule Kayu and Kute Tanyung villages, Kecamatan Bukit Kabupaten Bener Meriah, which are the two villages where KPM UIN Ar-Raniry students be placed in 2024. The data collection process was carried out through indepth interviews, Small Group Discussions with students, observation and documentation studies . The research results show that interaction is a common action that everyone always carries out in their lives, both individually and in groups. The students who are taking the subject of Kuliah Pengabdian Kepada Masyarakat (KPM), their ability to interact with the community is very important in order to successfully carry out their work program well. The ability to interact will influence the success of KPM. The success of KPM students in Bukit District is influenced by 3 forms of interaction namely symbolic interaction, investigative interaction and pedagogical interaction. These three forms of interaction have been able to build effective collaboration with the community so that they can implement various programs that have been previously designed.